2018
DOI: 10.3389/fendo.2018.00311
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Fibroblast Growth Factor-23 Secretion in Bone Locally Contributes to Impaired Bone Mineralization in Chronic Kidney Disease in Mice

Abstract: Chronic kidney disease-mineral and bone disorder (CKD-MBD) is a systemic disorder of mineral and bone metabolism caused by CKD. Impaired bone mineralization together with increased bony secretion of fibroblast growth factor-23 (FGF23) are hallmarks of CKD-MBD. We recently showed that FGF23 suppresses the expression of tissue nonspecific alkaline phosphatase (TNAP) in bone cells by a Klotho-independent, FGF receptor-3-mediated signaling axis, leading to the accumulation of the mineralization inhibitor pyrophosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…Osteopontin secretion is indirectly downregulated by FGF23 signaling: lower availability of extracellular phosphate suppresses osteopontin expression (Murali et al, 2016b). Although, acting locally, also high systemically circulating FGF23 could modulate pyrophosphate metabolism (Murali et al, 2016a,b; Andrukhova et al, 2018). Moreover, alterations in vitamin D metabolism contribute to impaired bone mineralization in response to iFGF23.…”
Section: Ifgf23 Directly Impairs Bone Mineralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteopontin secretion is indirectly downregulated by FGF23 signaling: lower availability of extracellular phosphate suppresses osteopontin expression (Murali et al, 2016b). Although, acting locally, also high systemically circulating FGF23 could modulate pyrophosphate metabolism (Murali et al, 2016a,b; Andrukhova et al, 2018). Moreover, alterations in vitamin D metabolism contribute to impaired bone mineralization in response to iFGF23.…”
Section: Ifgf23 Directly Impairs Bone Mineralizationmentioning
confidence: 99%
“…So, iFGF23 signaling results directly in impaired bone mineralization via TNAP suppression. Notably, current knowledge is based on FGF23-knockout models, thereby not reflecting the interplay of iFGF23 and cFGF23 (Murali et al, 2016a,b; Andrukhova et al, 2018).…”
Section: Ifgf23 Directly Impairs Bone Mineralizationmentioning
confidence: 99%
“…Finally, in CKD, Fgf23 mRNA transcription is increased in bone cells early in the disease course, likely due to inflammatory signals and iron deficiency, which are both inducers of FGF-23. This leads to normal or high serum phosphate and a high iFGF-23/cFGF-23 ratio (24,42,45,51,53). However, with increasing impairment of kidney function, renal phosphate excretion is reduced, leading to a progressive increase in serum phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…For this goal, osteocytes produce crystallization and mineralization inhibitors (SIBLING proteins such as osteopontin and MEPE, fetuin-A or tethering elements' component -perlecan) as well as enzymes for active digestion of their direct surroundings (such as matrix metalloproteinases) (96,99,100,101) to prevent spontaneous calcium and phosphorus precipitation around the cell (102,103) and are even able to dissolve bone minerals, as observed in lactation (10). Additional molecules involved in the process may be locally produced FGF23 and osteopontin, as animal studies suggested that increased local production of FGF23 by osteocytes reduces activity of alkaline phosphatase, leading to increased levels of pyrophosphate, a known mineralization inhibitor (104). However, following osteocyte death, the lack of crystallization inhibitors allows spontaneous mineralization of the lacuna and canaliculi, given the normally available calcium in the extracellular space.…”
Section: Mechanisms Of Lacunar Mineralizationmentioning
confidence: 99%